The impact of comprehensive prevention of mother-to-child HIV transmission in Dehong prefecture, Yunnan province, 2005-2010: A hard-hit area by HIV in Southern China. - Shan, Duo; Sun, Jiangping; Khoshnood, Kaveh; Fu, Jeannia; Duan, Song; Jiang, Chengqin; Zhang, Yan; Bulterys, Marc; Guo, Haoyan; Sante, Michael; Liu, Hui; Hu, Yiyun (International journal of STD & AIDS, 2013)
The burden of HIV/AIDS in China has been disproportionately concentrated in Yunnan Province, where in Dehong prefecture, HIV prevalence rates among pregnant women has reached 1.3% in 2003, a rate that is indicative of a generalized epidemic. Since then, there have been extensive efforts to expand prevention to reduce mother-to-child transmission (MTCT) in this high-prevalence region. These intensified MTCT reduction efforts and their impact on MTCT are yet to be examined. We described the changes in access to HIV screening and antiretroviral therapy (ART) among pregnant women from 2005 to 2010 in this region and the corresponding reduction in MTCT over this period. Between 2005 and 2010, the annual number of pregnant women screened for HIV in Dehong Prefecture more than doubled. The proportion of pregnant women screened for HIV rose from an estimated 15-20% to 99.8%, and the proportion of HIV-infected pregnant women receiving ART increased from 63% to 99%. We estimate that the proportion of children born with HIV to HIV-infected mothers decreased from 15.4% to 7.2% over this period. Sustained low-level MTCT following comprehensive interventions in this region is encouraging. Over the last decade, comprehensive PMTCT efforts, coupled with national and local government policy support in this area appear to be effective.